CLASS OF STANDARD DEVIATION OF LEFT VENTRICLE EJECTION FRACTION AND ULTRASOUND INDECES OF LEFT HEART CHAMBERS BY ATRIUM FIBRILLATION - YabluchanskayaТ.P.; Vakulenko, I.P. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Conducted ultrasound researches of 2 representative groups of patients with continuous atrium fibrillation (AF – research group) and sinus rhythm (SR – comparing group) has shown that there was not only an increased left heart size, but also a violation in structural relations between its chambers, mostly of left ventricle. In ultrasound research of patients with AF it is possible to calculate left atrium and aorta sizes according the protocols recommended for SR, unlike left ventricle size calculation which demands more number of beat-to-beat measurings.